Designing Historia Card for Indonesian National Disintegration Learning - Intan Nuraini (Yupa: Historical Studies Journal, 2026)
This study examines the design and feasibility of Historia Card, a card-based instructional medium for learning Indonesian national disintegration in senior high school history education. The problem addressed is the tendency of history lessons on conflict, integration, and national cohesion to be delivered through verbal explanation, which limits students’ contextual understanding and classroom participation. Using qualitative design research, the study involved needs analysis, prototype design, expert review, revision, and feasibility evaluation through interviews, classroom observation, questionnaires, and documentation. The findings indicate that teachers and students required a practical, visual, and discussion-oriented medium that could organize historical events, actors, causes, consequences, and values of national integration. Historia Card was therefore designed as a quartet-card medium combining concise historical information, visual cues, categorization tasks, and collaborative play. Expert validation and user responses showed that the medium was very feasible, practical, and engaging. The study contributes to history education by demonstrating how non-digital game-based media can support contextual historical understanding while remaining accessible for classroom use.